The Use of Sewage Sludge Ash (SSA) as Partial Replacement of Cement in Concrete - Doh, Shu Ing; Chin, Siew Choo; Tan, Kim Guan; Suil, Adilen (Asian Research Publishing Network (ARPN), 2016)
The production of sewage sludge (SS) from waste water treatment plant is increasing all over the world. Disposal of sewage sludge is becoming a serious environmental issues to our society. Sewage sludge which contain high heavy metal is no longer suitable to be used as fertilizer. Besides, the land fill, which is the main disposal method has also posed threat to leachate of heavy metal from the sewage sludge to the soil. Due to fast urbanization, the demand of cement has increased alarmingly. This will lead to increased cement production and emission of carbon dioxide because the cement industry one of the major contributor of carbon dioxide emission. Hence, the research for replacement of cement using sewage sludge ash is essential to reduce both the emissions of carbon dioxide and the disposal problem of sewage sludge ash. In this investigation, sewage sludge ash has been used as partial cement replacement in concrete. The sewage sludge is incinerated at the temperature of 600°C and a duration of three hours. The incinerated sewage sludge ash is sieved through sieve size of 150 µm. Four different percentages of sewage sludge ash (SSA) is used to replace the cement in the concrete. XRD and XRF tests were carried to compared the result between SS, SSA and cement. The test conducted on concrete in this investigation were slump test, water absorption and water absorption. Results show that SSA has the potential to replace cement since there are high similarity in major chemical component of SSA compared to cement. The replacement of cement in concrete with 5% SSA has shown lower water absorption and increase compressive strength of concrete up to 10% as compared with the control samples